Medication Competence, Numeracy, and Health Literacy - Kevin M. Gutierrez; Lawrence D. Cohn (SLACK Incorporated, 2019)
Two studies investigated the association between medication literacy and numeracy. Study 1 revealed an association between both variables in a sample of adults. Study 2 replicated the finding in a sample of parents of young children, even after controlling for level of parental health literacy. Both studies employed the Medication Literacy in Spanish and English (MedLitRxSE) assessment tool. Objective and subjective numeracy scores were significantly correlated with MedLitRxSE scores in both studies, suggesting that interventions for reducing medication errors might benefit by simplifying the numerical information presented in medication instructions.